Corn oil microcapsule for asphalt self-repairing and preparation method thereof
By using corn oil as the capsule core material, corn oil microcapsules with particle size less than 30μm were prepared, which solved the problems of high cost and poor stability of existing asphalt microcapsules capsule core materials, and achieved efficient self-repairing effect of asphalt pavement.
Patent Information
- Application Number
- CN202411671182.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing asphalt microcapsule core materials are costly and have poor stability, making it difficult to effectively improve the self-repair performance of asphalt pavement.
Corn oil is used as the capsular material for the microcapsules, and corn oil microcapsules with a particle size less than 30 μm are prepared by combining emulsifier, curing agent and shell material.
It realizes low-cost, easy-to-preparation and high-stability asphalt self-repair microcapsules, which improves the self-repair performance of asphalt pavement, and the repair rate reaches 36%-41%.
Smart Images

Figure CN119499996A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt pavement repair materials, and in particular to corn oil microcapsules for asphalt self-repairing and a preparation method thereof. Background Art
[0002] Asphalt is a material with certain self-repairing properties, that is, during the use of asphalt pavement, micro-damage and micro-cracks can be self-repaired to a certain extent. However, the repair effect is usually unsatisfactory and cannot offset the damage caused during normal use. In order to extend the service life of asphalt pavement, it is crucial to maintain and repair it at the right time. Previous studies mainly enhanced the self-repairing properties of asphalt materials through induction heating, capsules with healing agents, and nanoparticles. Among them, microcapsule technology, as an emerging, low-carbon and practical technology, has become an important research approach to enhance the self-repairing ability of asphalt.
[0003] At present, there are many kinds of regeneration agents used as microcapsule core materials, and each has its own advantages and disadvantages. In China, some scholars have used self-made regeneration agents mixed with base oil, plasticizer, antioxidant, structural repair agent and penetrant in different proportions, but the preparation cost is high and the control requirements for the proportion of each additive are quite strict. For this reason, it has not been widely promoted.
[0004] In view of the above situation, researchers gradually tend to choose green and pollution-free regeneration agents such as vegetable oil in the selection of microcapsule core materials. Corn oil is extracted from corn germ and refined through a series of complicated physical processes such as deacidification, dephosphorization, degumming, decolorization and dewaxing. It appears as a clear and transparent golden liquid. Corn oil is rich in vitamins, minerals and a large amount of unsaturated fatty acids, mainly including oleic acid and linoleic acid. Experiments show that after corn oil and emulsifier are fused, the oil droplets are in good condition, have excellent fluidity and permeability, and can repair aged asphalt to a certain extent.
[0005] Therefore, in view of the various problems presented by the current asphalt microcapsule core materials, it is necessary to develop an asphalt microcapsule with corn oil as the core material. Summary of the invention
[0006] The present invention aims to solve the limitations of existing asphalt microcapsule core materials such as high cost and poor stability, and to provide an asphalt self-repairing microcapsule that is easy to prepare, has strong self-stability and good regeneration effect.
[0007] The present invention specifically adopts the following technical solutions:
[0008] On the one hand, the present application provides a corn oil microcapsule for asphalt self-repairing, which is prepared by 7 parts of emulsifier, 6 parts of curing agent, 55 parts of corn oil, 50 parts of shell material and 125 parts of water in parts by weight;
[0009] The shell material is melamine powder, urea granules and formaldehyde solution; the emulsifier is sodium dodecylbenzene sulfonate; and the curing agent is resorcinol.
[0010] Furthermore, in the shell material, the mass ratio of melamine, urea and formaldehyde is 1:2:7.
[0011] Furthermore, the corn oil microcapsules have a particle size of less than 30 μm, accounting for 75% of the total, and the average particle size is 23.7 μm, belonging to micron-level microcapsules.
[0012] On the other hand, the present application provides a method for preparing a self-repairing asphalt corn oil microcapsule according to the present invention, comprising the following steps:
[0013] 1. Weigh the emulsifier, curing agent, corn oil and deionized water according to weight;
[0014] 2. Add the weighed emulsifier into deionized water, stir at a constant speed for 30 minutes, pour corn oil into the solution, and emulsify it in a high-speed shear emulsifier for 1 hour to obtain a capsule core emulsion;
[0015] 3. Add the shell solution into deionized water; stir in a 75°C water bath until the urea is completely dissolved, adjust the pH to 8, terminate the reaction after 1 hour, and wait for the solution to cool to room temperature to obtain a shell solution;
[0016] 4. Weigh melamine powder, urea granules and formaldehyde solution in proportion and pour them into the capsule core emulsion in turn, add resorcinol, stir, raise the temperature of the mixed solution to 60°C, and adjust the pH to 3; after reacting for 4 hours, adjust the pH of the solution to 7;
[0017] 5. When the temperature drops to room temperature, filter the turbid liquid;
[0018] 6. Wash and dry to obtain self-repairing asphalt corn oil microcapsule powder.
[0019] Furthermore, in the preparation of the capsule core emulsion in step 2, the uniform stirring and high-speed shearing rates are 400 r / min and 1.2 kr / min, respectively.
[0020] Furthermore, in the preparation of the shell solution in step 3, the stirring rate is 400 r / min.
[0021] On the other hand, the present application provides asphalt to which corn oil microcapsules according to the aforementioned self-repairing asphalt are added, wherein the corn oil microcapsules account for 4%-8% of the mass of the asphalt and the Rq value repair rate is 36%-41%.
[0022] Furthermore, the surface of the corn oil microcapsules is rough and in close contact with the asphalt. Microcracks penetrate the microcapsules to cause them to rupture and release the corn oil capsule core. The corn oil diffuses and fills the cracks through capillary action, and the cracks become narrower after 1 hour.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention uses corn oil as a regeneration agent, which is low-carbon, environmentally friendly and has good regeneration performance. The corn oil microcapsules prepared by the present invention are observed and analyzed by fluorescence microscopy, and the particle size distribution is concentrated in 0-30 μm, which is lower than the microcapsule particles (40 μm-2 mm) in the existing research, and the performance of the asphalt pavement is less affected after being added to the asphalt pavement.
[0025] The corn oil microcapsules prepared by the present invention were tested by a comprehensive thermal analyzer, and it was found that the increase in temperature would not have a significant impact on the mass loss of the sample, which ensured the stability of the asphalt mixing stage; the present invention used an atomic force microscope to observe the microscopic surface of the self-repairing asphalt and found that after adding corn oil microcapsules, the surface morphology of the asphalt sample changed to varying degrees, and the self-repairing ability of the asphalt was improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The figure is a flow chart of the preparation of microcapsules of the present invention.
[0028] Figure 2 This is a microscopic morphology of the microcapsule of the present invention.
[0029] Figure 3 This is the particle size distribution diagram of the microcapsules of the present invention.
[0030] Figure 4 Thermogravimetric analysis test results of the microcapsules of the present invention are shown in FIG.
[0031] Figure 5 FTIR spectra of asphalt with different microcapsule dosages of the present invention
[0032] Figure 6 This is the healing behavior of the self-repairing asphalt of the present invention.
[0033] Figure 7 This is the apparent morphology of a single microcapsule of the present invention.
[0034] Figure 8 This is the surface morphology of the self-repairing asphalt of the present invention. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] The present invention provides a corn oil microcapsule for asphalt self-repairing. The microcapsule comprises a capsule core and a wall material wrapping the capsule core. The capsule core is mainly composed of corn oil. The wall material contains melamine, urea and formaldehyde. The mass ratio of melamine, urea and formaldehyde is 1:2:7.
[0037] In order to deepen the understanding of the present invention, the technical scheme of the present invention is further described in combination with embodiments and experiments, but the present invention is not limited to the following implementation scenarios.
[0038] Embodiment 1:
[0039] Preparation of corn oil microcapsules (see Figure 1 ).
[0040] 1. Add 7 parts of sodium dodecylbenzene sulfonate into 100 ml of water and stir at a speed of 400 r / min for 30 min; pour 55 parts of corn oil into the solution and emulsify it under a high-speed shear emulsifier at a shear speed of 1.2 kr / min for 1 h to obtain a capsule core emulsion.
[0041] 2. Add 50 parts of melamine, urea and formaldehyde in a ratio of 1:2:7 to 25 ml of deionized water; stir in a 75°C water bath at 400 r / min until the urea is completely dissolved, adjust the pH to 8, terminate the reaction after 1 hour, and wait for the solution to cool to room temperature to obtain a shell solution.
[0042] 3. Pour the prepolymer solution into the emulsified solution and add 6 parts of resorcinol, stirring; raise the temperature of the mixed solution to 60°C and adjust the pH to 3; after reacting for 4 hours, adjust the pH of the solution to 7; when the temperature drops to room temperature, filter the turbid liquid, wash, and dry to obtain microcapsule powder S1.
[0043] from Figure 2It can be seen that the corn oil microcapsule particles present an irregular spherical structure in the solution. Figure 3 It can be seen that the particle size distribution range of corn oil microcapsules is mainly 0-30μm, with an average particle size of 23.7μm, which belongs to micron-sized microcapsules.
[0044] Comparative Example 1:
[0045] The method of Example 1 is followed, except that in step 3, after the prepolymer solution is poured into the emulsified solution, resorcinol is not added, and the mixture is directly stirred to obtain microcapsule powder S2. No resorcinol was added to S2 during the synthesis of the prepolymer, and the microcapsule powder S2 was tested for the stability of the capsule core content by using a petroleum ether soaking method. The results show that the addition of curing agent resorcinol can promote the adsorption of the shell material on the surface of the capsule core material, thereby increasing the capsule core content per unit mass of the microcapsule. Therefore, curing agent resorcinol should be added during the preparation of microcapsules to optimize the performance of the microcapsules.
[0046] Other examples were prepared with reference to Example 1:
[0047] Embodiment 2:
[0048] Prepare self-healing asphalt with 4% corn oil microcapsule dosage.
[0049] Steps 1-3 are consistent with those in Example 1, and the following steps are added thereto:
[0050] 4. Heat 200g of short-term aged asphalt to 160°C, add 8.3g of corn oil microcapsules, stir at a constant speed for 30 minutes, and then cool to room temperature.
[0051] 5. Reheat the 4% microcapsule asphalt to 160℃, absorb about 0.5g and drop it on a glass slide, place it in a 135℃ constant temperature box and wait for it to flow naturally until it is evenly spread on the glass slide, and let it stand at room temperature for subsequent tests.
[0052] Embodiment 3:
[0053] Prepare self-repairing asphalt with 8% corn oil microcapsule dosage. Steps 1-3 are consistent with Example 1, and the following steps are added thereto:
[0054] 4. Heat 200g of short-term aged asphalt to 160°C, add 17.4g of corn oil microcapsules, stir at a constant speed for 30 minutes, and then cool to room temperature to obtain self-repairing asphalt with 8% corn oil microcapsule dosage.
[0055] 5. Reheat 8% microcapsule asphalt to 160℃, absorb about 0.5g and drop it on a glass slide, place it in a 135℃ constant temperature box and wait for it to flow naturally until it is evenly spread on the glass slide, and let it stand at room temperature for subsequent tests.
[0056] Embodiment 4:
[0057] Asphalt mixtures were prepared by adding 0, 3wt%, 6wt%, 9wt% and 12wt% corn oil microcapsules S1 into the asphalt mixtures, respectively, taking the corn oil microcapsules required to improve the self-repairing performance of microcracks in the Marshall specimen of the standard asphalt mixture (cylinder with a diameter of 101.6±0.2mm×height of 63.5±1.3mm) as an example.
[0058] Preparation method:
[0059] First, the asphalt concrete mixer was preheated to 180°C, and then the set mass of preheated coarse and fine aggregates and asphalt were added. The mixer was started, and after mixing for 90 seconds, the set mass of hot mineral powder and corn oil microcapsules were added. The mixing was continued for 90 seconds, and the concrete was ensured to be within the mixing temperature range. The mixed asphalt concrete containing corn oil microcapsules was poured out from the mixing pot, and standard Marshall specimens containing different amounts of corn oil microcapsules were formed by compaction method.
[0060] Then, the original asphalt mixture without corn oil microcapsules and the standard Marshall specimens of asphalt mixtures containing different amounts of corn oil microcapsules were tested according to the asphalt mixture splitting test of the current industry standard "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTG E20-2011 to evaluate the effect of different amounts of corn oil microcapsules on the self-healing effect of asphalt mixtures. The effect of microcapsule dosage on the healing performance of corn oil microcapsule asphalt concrete was studied by the healing index HI3, which is defined as the maximum load ratio of the Marshall specimens of the self-healing asphalt mixture before and after healing.
[0061] Implementation effect: The test results are shown in the table. At first, with the increase of corn oil microcapsule dosage, the healing index of the asphalt mixture Marshall specimen gradually increased, indicating that the addition of microcapsules played a positive role in the healing performance of the asphalt mixture Marshall specimen. However, when the microcapsule dosage continued to increase, the healing index HI3 began to show a downward trend, indicating that the dosage of corn oil microcapsules is more suitable at about 6%.
[0062] Microcapsule dosage / % 0 3 6 9 12 <![CDATA[Healing Index / HI3]]> 2.1723 2.2648 2.3462 2.3378 2.2369
[0063] Example 5
[0064] The present invention uses a comprehensive thermal analyzer to analyze the microcapsule powder prepared in Example 1. The heating rate is 10° C. / min, and the experimental atmosphere is nitrogen.
[0065] Figure 4 This is the comprehensive thermal analyzer test result. Figure 4The TG, DSC and DTG curves of the microcapsules are given. From 0°C to 210°C, the mass of the sample remains almost unchanged, which ensures the stability of the asphalt mixing stage. Before 210°C, the decomposition rate is close to zero, which means that the increase in temperature does not have a significant effect on the mass loss of the sample. After that, the decomposition rate increases until it reaches a maximum decomposition rate of 12.4% / min at 377°C. This indicates that the microcapsules undergo strong chemical decomposition in this temperature range (210°C to 377°C).
[0066] Example 6
[0067] 0.1g of microcapsule asphalt with a dosage of 0%, 2%, 4%, and 6% was taken for direct testing. The infrared spectrometer was preheated for 30 minutes before testing, and then background scanning was performed under the same conditions, with a resolution of 4cm -1 , scanned 32 times, in absorption mode 500~4000cm -1 The FTIR spectrum was recorded within the range. After the infrared spectrum data of each sample was collected, the surface of the crystal plate was wiped and cleaned with kerosene. Three FTIR tests were performed at different locations for each sample, and the test results were basically consistent, indicating that the microcapsules were evenly distributed in the asphalt. The average of the three test results was obtained to ensure repeatability and overcome the errors caused by unstable measurement environment and uneven asphalt aging.
[0068] The test results are as follows Figure 5 As shown in the figure, the asphalt samples with 2%, 4%, and 6% microcapsule addition have a -1 The C=O stretching vibration absorption peak of saturated fatty acid ester at the asphalt sample changes significantly compared with the asphalt sample without microcapsules, and the peak amplitude increases with the increase of the dosage. This absorption peak can be regarded as the characteristic peak after the addition of microcapsules.
[0069] Example 7
[0070] In order to preliminarily investigate the salt resistance of corn oil microcapsules, 2g of microcapsules were weighed in 0wt%, 5wt%, and 10wt% NaCl solutions, respectively, and stirred for 120 minutes at a speed of 650r / min while maintaining a water bath temperature of 50℃, and then left to stand at room temperature for 24 hours. The petroleum ether immersion test was used to determine the core content of the microcapsules after immersion in the salt solution. Instead of grinding with a mortar, the microcapsules after immersion in the salt solution were dried and then directly immersed in petroleum ether. The purpose was to extract the corn oil precipitated by the salt solution through petroleum ether, calculate the precipitated content Y, and thus evaluate the salt resistance of corn oil microcapsules.
[0071] The test results are shown in the following table. It can be seen from the table that when the microcapsules are immersed in an aqueous solution, the amount of corn oil microcapsules precipitated is only 3%. As the concentration of the salt solution increases, the amount of corn oil precipitated also gradually increases. This may be due to the fact that a small amount of corn oil microcapsules are broken in a high concentration of NaCl solution. In the actual use of microcapsule asphalt pavement, only a small amount of microcapsules on the asphalt surface may contact the snow melting agent, so the concentration of the salt solution it contacts is relatively small, about 0wt~5wt%. The analysis table shows that corn oil microcapsules are immersed in a 10wt% NaCl solution and only precipitate 19.5% of corn oil regeneration agent, indicating that it has good salt resistance.
[0072]
[0073] Example 8
[0074] The present invention uses a fluorescence microscope to observe the corn oil microcapsule asphalt sample corresponding to Example 3. Asphalt will produce cracks after low-temperature treatment. The present invention uses liquid nitrogen to treat the sample in order to artificially create microcracks, so as to observe the healing behavior of the self-repairing asphalt. The specific steps are as follows:
[0075] Step 1, placing the corn oil microcapsule asphalt sample corresponding to Example 3 on a table;
[0076] Step 2: Take a spray of liquid nitrogen and spray it vertically towards the middle of the sample at a constant speed for 3 seconds, and let it stand for 5 minutes;
[0077] Step 3: Use the cold air setting of the blower to blow the water droplets on the asphalt surface until they evaporate naturally;
[0078] Step 4: Place the asphalt sample processed by the above three steps under a fluorescence microscope for observation, and record the entire process for 1 hour using video recording software.
[0079] The healing behavior of self-healing asphalt microcracks is shown in Figure 7. Through FM comparison, the evolution of microcracks in the asphalt sample of Example 3 was observed before and after being placed at room temperature for 1 hour. It can be observed in the figure that the microcracks penetrated several microcapsule particles, causing the microcapsules to release corn oil regeneration agent, which gradually diffused and filled the microcracks due to the capillary effect, forming capillary channels. After 1 hour, the cracks narrowed, and the self-healing of the asphalt was achieved.
[0080] Example 9
[0081] The present invention uses an atomic force microscope to test the corn oil microcapsule asphalt samples corresponding to each embodiment. The atomic force microscope (Dimension ICON type) adopts the tapping mode, the scanning range is 20μm×20μm, and the test temperature is room temperature. The test results are as follows Figure 7 , Figure 8 shown.
[0082] Figure 7 This is the surface morphology image of a single microcapsule particle in the self-repairing asphalt. Figure 7 It can be seen that the surface of the microcapsules in the asphalt is rough and can maintain an irregular spherical structure, indicating that the corn oil microcapsules are not destroyed during the asphalt mixing process and can still exist in the asphalt in a better form.
[0083] Figure 8 This is the surface morphology image of self-healing asphalt. Figure 8 It can be seen that after asphalt aging, the peak structure undergoes appropriate "development" and its distribution in the asphalt tends to be concentrated. After adding 4% and 8% microcapsules, the peak structure of the self-repairing asphalt undergoes a certain "shrinkage" compared with the aged asphalt, that is, the average area of the peak structure decreases to varying degrees, while the number and area proportion of the peak structure at the two microcapsule dosages increase to varying degrees. It can be seen that the addition of corn oil microcapsules reduces the impact of aging on the microscopic morphology of the asphalt surface.
[0084] In order to further quantitatively analyze the microscopic mechanism of microcapsules, the root mean square roughness Rq was used to quantitatively analyze the effect of different microcapsule dosages on the microscopic surface morphology of asphalt. The Rq of the four samples was calculated in a 40μm×40μm scanning range using NanoScope Analysis software, and the calculation results are shown in the following table.
[0085] Table: RMS roughness of each asphalt sample
[0086]
[0087] The Rq value of the aged asphalt sample is reduced by 5.31nm relative to the base asphalt. This is because the asphalt components undergo migration changes due to aging, the asphaltene and colloid content increases, and the multi-component phase of the asphalt tends to be homogenized, thereby reducing the difference in roughness.
[0088] The Rq values of 4% and 8% microcapsule asphalt samples were only reduced by 3.4nm and 3.14nm relative to the matrix asphalt, indicating that the microcapsules reduced the effect of asphalt aging on the Rq value and repaired the aged asphalt to a certain extent, with repair rates of 36% and 41%, respectively. This indicates that the addition and effective release of microcapsules reduced the agglomeration of asphaltene, promoted the accumulation and continuous growth of wax crystals, and slowed down the effect of aging on the peak structure, and the degree of slowing down increased with the increase in the amount of microcapsules. It can be seen that the corn oil regeneration agent released in the microcapsules reversed the above homogenization process, further verifying the ability of microcapsules to promote the repair of aged asphalt.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A corn oil microcapsule for asphalt self-repair, characterized in that: Prepared from 7 parts of emulsifier, 6 parts of curing agent, 55 parts of corn oil, 50 parts of shell material and 125 parts of water by weight; The shell material is melamine powder, urea granules and formaldehyde solution; the emulsifier is sodium dodecylbenzene sulfonate; and the curing agent is resorcinol.
2. The self-repairing asphalt corn oil microcapsule according to claim 1, characterized in that: In the shell material, the mass ratio of melamine, urea and formaldehyde is 1:2:
7.
3. The self-repairing asphalt corn oil microcapsule according to claim 2, characterized in that: The corn oil microcapsules with a particle size of less than 30 μm account for 75% of the total, and the average particle size is 23.7 μm, belonging to micron-level microcapsules.
4. The method for preparing self-repairing asphalt corn oil microcapsules according to claim 3, characterized in that: The steps include:
1. Weigh the emulsifier, curing agent, corn oil and deionized water according to weight; 2. Add the weighed emulsifier into deionized water, stir at a constant speed for 30 minutes, pour corn oil into the solution, and emulsify it in a high-speed shear emulsifier for 1 hour to obtain a capsule core emulsion; 3. Add the shell solution into deionized water; Stir in a 75°C water bath until urea is completely dissolved, adjust the pH to 8, terminate the reaction after 1 hour, and wait for the solution to cool to room temperature to obtain a shell solution; 4. Weigh melamine powder, urea granules and formaldehyde solution in proportion and pour them into the capsule core emulsion in turn, add resorcinol, stir, raise the temperature of the mixed solution to 60°C, and adjust the pH to 3; after reacting for 4 hours, adjust the pH of the solution to 7; 5. When the temperature drops to room temperature, filter the turbid liquid; 6. Wash and dry to obtain self-repairing asphalt corn oil microcapsule powder.
5. The method for preparing self-repairing asphalt corn oil microcapsules according to claim 4, characterized in that: In the preparation of the capsule core emulsion in step 2, the uniform stirring and high-speed shearing rates are 400 r / min and 1.2 kr / min, respectively.
6. The method for preparing self-repairing asphalt corn oil microcapsules according to claim 4, characterized in that: In the preparation of the shell solution in step 3, the stirring rate is 400 r / min.
7. Asphalt added with the self-repairing asphalt corn oil microcapsules according to claim 3, characterized in that: Corn oil microcapsules account for 4%-8% of the mass of asphalt, and the Rq value repair rate is 36%-41%.
8. The asphalt according to claim 7, characterized in that The surface of the corn oil microcapsules is rough and in close contact with the asphalt. Microcracks penetrate the microcapsules to cause them to rupture and release the corn oil capsule core. The corn oil diffuses and fills the cracks through capillary action, and the cracks become narrower after 1 hour.